Impact of Event Scale (IES): Psychometric properties in a Spanish sample with hereditary cancer risk - Costa-Requena, Gema; Garcia-Garijo, Mercedes; Richart Aznar, Paula; Segura-Huerta, Ángel (Revista de Psicopatología y Psicología Clínica, 2022)
Abstract: This study assessed the psychometric properties of the Impact of Event Scale (IES) in a Spanish sample at increased risk of hereditary cancer and the contribution of socio-demographic and clinical characteristics to predict cognitive intrusions and avoidance. A total of 766 patients participated in this cross-sectional study. Psychometric analyses of the IES were performed using exploratory and confirmatory factor analyses. The influences of socio-demographic and clinical characteristics were determined using multiple linear regression analyses. The exploratory analysis supported the original two-factor solution of the IES, and the confirmatory analysis added the cross-factor loading for item 12, characteristic for this population. Related to the socio-demographic and clinical variables, patient affected by cancer (β = -.19), sex (β = .15), previous psychiatric treatment (β = -.10), and age (β = -.08), were significant predictors of the intrusion subscale. Patient affected by cancer (β = -.19), sex (β = .13), and previous psychiatric treatment (β = -.14) were significant predictors of the avoidance subscale. Keywords: Cognitive symptoms; psychometrics; genetic counseling; hereditary cancer; emotional distress. Escala del Impacto del Estresor (EIE): Propiedades psicométricas en una muestra española con riesgo de cáncer hereditario Resumen: Este estudio evaluó las propiedades psicométricas de la Escala de Impacto del Estresor (EIE) en una muestra española con alto riesgo de cáncer hereditario, y la contribución de las características sociodemográficas y clínicas para predecir cogniciones de intrusión y evitación. Un total de 766 pacientes participaron en un diseño transversal. Los análisis psicométricos se realizaron a través de análisis factoriales exploratorios y confirmatorios. La influencia de las características sociodemográficas y clínicas se determinó llevando a cabo regresiones múltiples. El análisis exploratorio confirmó la solución original bifactorial del EIE, y el análisis confirmatorio añadió la carga factorial cruzada del ítem 12, que caracteriza a esta población. En las características sociodemográficas y clínicas, paciente afecto de cáncer (β = -.19), sexo (β = .15), antecedentes de tratamiento psiquiátrico (β = -.10), y edad (β = -.08), fueron predictores significativos de la subescala de intrusión. Paciente afecto de cáncer (β = -.19), sexo (β = .13), y antecedentes de tratamiento psiquiátrico (β = -.14) fueron predictores significativos de la subescala de evitación. Palabras clave: síntomas cognitivos; psicometría; consejo genético; cáncer hereditario; malestar emocional.